2021
DOI: 10.1002/icd.2284
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between emergent drawing, emergent writing, and visual‐motor integration in preschool children

Abstract: Drawing and writing are two major representational systems with many common aspects. Each also has its own system of rules, characterized by different degrees of visual realism and conventionality. The relationship between them at their emergence and the contribution of perceptual and motor skills to their development have been under‐investigated, leading to discordant study results. This study investigated the emergence of the ability to draw and write and the association between these two processes in 3‐ to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
9
0
2
Order By: Relevance
“…This finding supports the theory that besides fine motor performance there are other performance components needed for handwriting readiness. In previous research it is reported that besides fine motor coordination also visual-motor integration, as measured with the Developmental Test for Visual-Motor Integration (Beery-VMI) [15], is an important performance component [13,14,25]. Besides fine motor coordination and visualmotor integration, sustained attention was also descripted a predictive factor of handwriting attainment [9,26,27].…”
Section: Plos Onementioning
confidence: 99%
“…This finding supports the theory that besides fine motor performance there are other performance components needed for handwriting readiness. In previous research it is reported that besides fine motor coordination also visual-motor integration, as measured with the Developmental Test for Visual-Motor Integration (Beery-VMI) [15], is an important performance component [13,14,25]. Besides fine motor coordination and visualmotor integration, sustained attention was also descripted a predictive factor of handwriting attainment [9,26,27].…”
Section: Plos Onementioning
confidence: 99%
“…La investigación también revela que los niños(as) pequeños(as) desarrollan sus habilidades de escritura simultáneamente a sus habilidades de dibujo y pueden diferenciar los propósitos y los procesos, así como los puntos comunes y las diferencias entre sistemas (Pinto & Incognito, 2021). Asimismo, los estudios indican que participar en el proceso usando tanto dibujos como escritos puede incitar nuevas ideas y formas de comunicación entre ellos (Bezemer & Kress, 2008;Short et al, 2000).…”
Section: Notas De Campounclassified
“…Segundo, nuestro análisis muestra las consecuencias involuntarias de realizar presunciones sobre las intenciones o significados que los niños(as) asignan a sus dibujos, marcas o elementos escritos de sus composiciones multimodales, que a menudo se entrelazan de forma intencionada (Bezemer & Kress, 2008;Levin & Bus, 2003;Olshansky, 2008;Pinto & Incognito, 2021;Sidelnick & Svoboda, 2000). Implica que los educadores(as) iniciales y los padres/ madres/cuidadores(as) deben resistir la tentación de interpretar las composiciones de los niños(as) sin consultarlo con los(as) jóvenes autores(as).…”
Section: Conclusión E Implicanciasunclassified
“…Young children use varied forms of written communication to share their ideas with others and to demonstrate their understanding that print conveys meaning. Research shows that drawing and writing share many representational capacities as young children often use similar social, physical, and cognitive processes when using materials to construct a picture or a piece of writing (Pinto & Incognito, 2021). This may be one reason that so much writing happens in the art area in early childhood classroom as the presence of materials and the context of sharing ideas promotes children to compose and use their handwriting and invented spelling skills (Quinn, Gerde, & Bingham, 2021).…”
Section: Guidance For Best Writing Practicesmentioning
confidence: 99%